2006
DOI: 10.1007/11866763_21
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric Curvature Patterns for Colonic Polyp Detection

Abstract: Abstract.A novel approach for generating a set of features derived from properties of patterns of curvature is introduced as a part of a computer aided colonic polyp detection system. The resulting sensitivity was 84% with 4.8 false positives per volume on an independent test set of 72 patients (56 polyps). When used in conjunction with other features, it allowed the detection system to reach an overall sensitivity of 94% with a false positive rate of 4.3 per volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 10 publications
1
41
0
Order By: Relevance
“…The observed sensitivity was comparable to the sensitivity of radiologists using CTC [7], [15], [16] and competed with other CAD systems [7]- [9], [26]. It was also shown that the CAD system generalizes well to data sets from different medical centers.…”
Section: Discussion/conclusionmentioning
confidence: 52%
See 1 more Smart Citation
“…The observed sensitivity was comparable to the sensitivity of radiologists using CTC [7], [15], [16] and competed with other CAD systems [7]- [9], [26]. It was also shown that the CAD system generalizes well to data sets from different medical centers.…”
Section: Discussion/conclusionmentioning
confidence: 52%
“…Yoshida and Näppi used linear and quadratic discriminant classifiers [21], [22], [25] as well as Jerebko et al [26]. Wang et al [27] used a two-level classifier with a further unspecified linear discriminant classifier in the second level.…”
Section: A Related Workmentioning
confidence: 99%
“…We propose a stratified learning framework including (supervised) objectspecific image segmentation, segmentation feature extraction, robust object classification and importance regression (taking into account the segmentation ambiguity and uncertainty). Segmentation has been extensively explored for various medical imaging purpose [27,15,29,8,22,11,24], but explicit descriptive feature extraction and analysis on statistically characterizing segmentation outputs, for object classification and robust staging of cancer (as estimate of object key attributes), has not been much studied. In this paper, we focus on finding and analyzing polyps 1 , the precursors of colon cancer, but the proposed method can be extended to other medical imaging applications (e.g., lung nodule detection), or generic object segmentation and detection tasks in 3D range, LIDAR or spatial-temporal volumetric data.…”
Section: Introductionmentioning
confidence: 99%
“…It can be heuristic, non-probabilistic [15,29,8,24], or data-driven learned and probabilistic [12]. In [12], a compositional polyp segmentation framework is proposed (locating possible polyp tips; finding inside/outside polyp surface voxels; and optimizing polyp boundaries), by supervisedly learning the medical experts' knowledge as the annotated polyp boundary curves in a database.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, modeling through spherical harmonics [10], surface normal overlap [17] and other curvature-based methods have been developed [1,26]. The use of small to moderate [5,8,26] and of large [25] feature sets followed by a more sophisticated classification mechanism have also been explored.…”
Section: Introductionmentioning
confidence: 99%